Stvacintāmaṇi of Bhaṭṭa Nārāyaṇa the wish-fulfilling jewel of praise - Bhaṭṭanārāyaṇa ca. 9. Jh.; Pandit, Moti Lal 1947- (New Delhi Dev Publishers & Distributors, 2023)
Hymns, chiefly to Śiva (Hindu deity), expounding the viewpoint of the Trika school in Hindu philosophy
Hymns, chiefly to Śiva (Hindu deity), expounding the viewpoint of the Trika school in Kashmir Śaivism
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Siva -- (Hindu deity) -- Prayers and devotions; Hindy hymns, Sanskrit; Kashmir Śaivism; Devotional literature; Prayers; Kommentar